Aldosterone-producing nodules and CYP11B1 signaling correlate in primary aldosteronism. Issue 2 (10th January 2022) - Lin, Jui-Hsiang; Peng, Kang-Yung; Kuo, Yu-Ping; Liu, Hsuan; Tan, Chin-Ming Bertrand; Lin, Yuh-Feng; Chiu, Hui-Wen; Lin, Yen-Hung; Chen, Yung-Ming; Chueh, Jeff S; Wu, Vin-Cent
Abstract : Autonomous cortisol secretion (ACS) could be found in some patients with unilateral primary aldosteronism (uPA). However, the histopathological patterns of uPA with concurrent ACS have not been well elucidated. The adrenal gland with the adenoma from 61 uPA patients who underwent unilateral adrenalectomy were assessed by immunohistochemistry. Bioinformatics analysis, including the Cancer Genome Atlas (TCGA) and Kyoto Encyclopedia of Genes and Genomes, was applied. The prevalence of multiple aldosterone-producing nodules or micronodules (mAPN/mAPM) was 65.6% (40/61) among our uPA patients. Concurrent ACS was identified in 32% of this uPA cohort; they were associated with the interaction of larger tumor size (>1.98 cm) and mAPN/mAPM (odds ratio = 3.08, P = 0.004). Transcriptome analysis uncovered a dominant enrichment of HSD3B7 overexpression ( P = 0.004) in the adenomas of the histopathologically classical adrenal uPA lesions with concomitant mAPN/mAPM, compared with those uPA adenomas without concurrent surrounding mAPN/mAPM. We identified a novel linkage of enhanced steroidogenic genes of HSD3B7 expression concurrent with the downstream higher CYP11B1 expression; further relationship was confirmed by immunohistochemical staining and validated by TCGA bioinformatics. The presence of mAPN/mAPM in uPA patients had lower rate for biochemical success after adrenalectomy ( P = 0.047). In summary, two-thirds of uPA patients had concomitant mAPN/mAPM; 1/3 of uPA patients had concurrent ACS. Steroidogenic HSD3B7/CYP11B1 signaling was associated with uPA adenomas with surrounding mAPN/mAPM. Interaction of larger adenoma size with the presence of mAPN/mAPM was linked to co-existing ACS. Such uPA patients with concomitant mAPN/mAPM had lower rate of biochemical success.